2015
DOI: 10.1186/1476-072x-14-5
|View full text |Cite
|
Sign up to set email alerts
|

Emergency care facility access in rural areas within the golden hour?: Western Cape case study

Abstract: BackgroundRoad Safety is a major cause of death around the world and South Africa has one of the highest road fatality rates. Many measures, engineering and medical, are investigated. However, analysis of the accessibility of emergency care facilities is often overlooked. This paper aims to fill the gap between pre-crash engineering solutions and literature on trauma injuries and emergency care procedures. The focus is on the role that accessibility to emergency care facilities in rural areas plays, given that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 5 publications
0
30
1
Order By: Relevance
“…Therefore, in some countries, including South Africa, KSA and Portugal, distance to key populations is considered when planning on building new health facilities. [13][14][15] Saeed et al 16 found that the longer the distance travelled to primary healthcare centres in Riyadh, the lower the patients' satisfaction, with 39% of patients considering the primary healthcare centre far or very far. However, in our study, distance was not an issue, and we did not observe any association between type of healthcare facilities used or distance to healthcare facilities, and health outcomes or use of health services in KSA.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in some countries, including South Africa, KSA and Portugal, distance to key populations is considered when planning on building new health facilities. [13][14][15] Saeed et al 16 found that the longer the distance travelled to primary healthcare centres in Riyadh, the lower the patients' satisfaction, with 39% of patients considering the primary healthcare centre far or very far. However, in our study, distance was not an issue, and we did not observe any association between type of healthcare facilities used or distance to healthcare facilities, and health outcomes or use of health services in KSA.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed emergency care may also contribute to long‐term morbidity and mortality . Current trauma protocols emphasize the importance of rapid definitive medical care through the concepts of the “golden hour” and “scoop and run.” Past research suggests significant benefits of expedited medical care following acute injuries in the community or the battlefield . Delayed emergency care following agricultural injury has yet to be quantified and the potential adverse long‐term outcomes remain mostly speculative .…”
mentioning
confidence: 99%
“…The results of other studies have shown that the distance of road emergency bases from each other is an effective factor in locating the road emergency bases [18][19][20]. Therefore, according to the importance of the distance of road emergency bases from each other, determining an index or formula to find the proper distance of these bases from each other is very important and should be a high priority for future studies.…”
Section: Discussionmentioning
confidence: 99%